2000
DOI: 10.1172/jci8337
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TGF-β signaling contributes to autoimmune pancreatitis

Abstract: Figure 4Changes of cytokines. Increased IL-1β was observed in transgenic mice, whereas IL-1β was not detected in wild-type littermates. IL-2, IFN-γ, and IL-10 were all expressed at higher levels in the pancreata of pS2-dnRII transgenic mice compared with those of wildtype littermates. Expression of TNF-α was increased after the induction of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 39 publications
3
54
0
Order By: Relevance
“…More recently, selective pancreatic expression using the trefoil peptide promoter increased susceptibility to cerulean-induced pancreatitis (30). Previous studies expressing T␤RII⌬k in mesenchymal cells, whose growth or differentiation is likely to be promoted rather than inhibited by TGF␤ stimulation, probably better reflect the present study.…”
Section: Fibroblast-specific Perturbation Of Tgf␤ Signalingsupporting
confidence: 54%
“…More recently, selective pancreatic expression using the trefoil peptide promoter increased susceptibility to cerulean-induced pancreatitis (30). Previous studies expressing T␤RII⌬k in mesenchymal cells, whose growth or differentiation is likely to be promoted rather than inhibited by TGF␤ stimulation, probably better reflect the present study.…”
Section: Fibroblast-specific Perturbation Of Tgf␤ Signalingsupporting
confidence: 54%
“…Loss of TGF-␤ signaling in TGF-␤ dominant negative mutant mice might contribute to AIP (Hahm et al, 2000). TGF-␤ gene expression in our mouse model was not different compared with control mice (data not shown).…”
Section: Uchida Et Almentioning
confidence: 64%
“…TGF-␤ is a potent inhibitor of MMP gene expression in mesenchymal cells (50 -52). Matrix degrading activity is constitutively elevated in mice with genetic disruption of TGF-␤ signaling, highlighting the physiological significance of negative MMP regulation by TGF-␤ (53). Previous studies investigating the mechanistic basis of MMP-1 inhibition demonstrated that IL-1 receptor expression was reduced by TGF-␤ treatment in a variety of cell types (25,54).…”
Section: Discussionmentioning
confidence: 99%